1999
DOI: 10.1016/s1097-2765(00)80342-1
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical Mutant Phenotypes of the Receptor EphB4 and Its Specific Transmembrane Ligand ephrin-B2 in Cardiovascular Development

Abstract: Ephrin-B2 is a transmembrane ligand that is specifically expressed on arteries but not veins and that is essential for cardiovascular development. However, ephrin-B2 is also expressed in nonvascular tissues and interacts with multiple EphB class receptors expressed in both endothelial and nonendothelial cell types. Thus, the identity of the relevant receptor for ephrin-B2 and the site(s) where these molecules interact to control angiogenesis were not clear. Here we show that EphB4, a specific receptor for ephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
551
0
4

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 640 publications
(567 citation statements)
references
References 41 publications
(1 reference statement)
12
551
0
4
Order By: Relevance
“…Indeed, EphB3 Ϫ/Ϫ animals show abnormalities in lung fibrillin-1 distribution, suggesting a role of this receptor for efficient lung secondary septation. As the lung phenotype of EphB3 knockout is rather mild compared with that seen in ephrinB2 ⌬V/⌬V mice, additional interactions within the vascular endothelium, as suggested by the phenotypes of ephrinB2 and EphB4 knockout mice (Wang et al, 1998;Adams et al, 1999;Gerety et al, 1999) and the expression of EphB2 and EphA4 on the vasculature (Fig. 2), likely also contribute to lung capillary development.…”
Section: Eph Receptors and Ephrins Demarcate Interactions Within The mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, EphB3 Ϫ/Ϫ animals show abnormalities in lung fibrillin-1 distribution, suggesting a role of this receptor for efficient lung secondary septation. As the lung phenotype of EphB3 knockout is rather mild compared with that seen in ephrinB2 ⌬V/⌬V mice, additional interactions within the vascular endothelium, as suggested by the phenotypes of ephrinB2 and EphB4 knockout mice (Wang et al, 1998;Adams et al, 1999;Gerety et al, 1999) and the expression of EphB2 and EphA4 on the vasculature (Fig. 2), likely also contribute to lung capillary development.…”
Section: Eph Receptors and Ephrins Demarcate Interactions Within The mentioning
confidence: 99%
“…EphrinB2, a transmembrane protein endowed with its own signaling potential, is expressed on arterial and lymphatic endothelial cells (ECs) as well as perivascular cells, and its receptor, EphB4, is largely confined to venous and lymphatic endothelium (Wang et al, 1998;Adams et al, 1999;Gerety et al, 1999;Makinen et al, 2005) Experiments using gene targeted mice have shown that these proteins are crucial for embryonic sprouting angiogenesis, and together with other family members could contribute greatly to specialization and maturation of vascular beds (Heroult et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ephrins do not function as typical soluble ligands for their receptors but, rather, must normally be membrane-bound to activate their receptors, through clustering or multimerization induction in a bidirectional signaling. Although initially characterized in the nervous system, ephrin A, ephrin B2, and EphB4 are expressed by endothelial cells and recent knockout studies have suggested key role for ephrin B2 and it EphB4 receptor during vascular development mainly in early angiogenic remodeling (Gerety et al, 1999). Moreover, ephrin B2 and EphB4 display remarkable reciprocal distribution patterns with ephrin B2 marking the endothelium of primordial arterial vessels while EphB4 marks the endothelium of primordial venous vessels (Adams et al, 1999).…”
Section: Ephrinsmentioning
confidence: 99%
“…Les CE artérielles du poisson zèbre, du poulet et de la souris expriment sélectivement l'éphrine-B2, la neuropiline 1 (NRP1), le récepteur notch3, le ligand de Notch Delta-like 4 et gridlock [5][6][7][8][9][10][11][9][10][11][12][13][14][15][16]. D'autres molécules sont spécifiquement exprimées par les CE veineuses, notamment EphB4, le récepteur du marqueur artériel éphrine-B2 [12]. Précocement, le récepteur neuropiline 2 est aussi présent à la surface des CE veineuses puis son expression se restreint aux CE lymphatiques plus tardivement [5,13].…”
Section: Les Marqueurs Moléculaires Spécifiques Des Artères Et Des Veunclassified